2021
DOI: 10.2174/1573396317999210111200222
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Primary Hypertension in Pediatric Patients: An Up-to-Date

Abstract: Background:: Arterial hypertension in children is considered a common alteration nowadays, mainly because obesity is a growing worldwide problem closely related to increased blood pressure. Childhood hypertension can be classified as primary or secondary, depending on the etiology. Primary or essential hypertension still has its pathophysiology not fully elucidated, and there is no consensus in the literature on most underlying mechanisms. In this review, genetic and environmental factors, including sodium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 239 publications
0
2
0
1
Order By: Relevance
“…These findings support the hypothesis that central obesity is a CVD risk factor that triggers other disorders, which usually emerge as comorbidities of central obesity [ 11 , 14 , 17 , 33 ]. Regarding to hypertension, the increasing trend of elevated blood pressure levels in childhood and adolescence in terms of primary hypertension has been mainly related to the also increasing trend of childhood obesity, but also to other factors such as prenatal and postnatal exposures, genetic factors, birth characteristics, dietary habits, or lifestyle factors [ 50 ]. Some of them have been shown to be related to primary hypertension independently of obesity, as evidenced for example by Rosner et al [ 51 ] in the case of high sodium intake.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the hypothesis that central obesity is a CVD risk factor that triggers other disorders, which usually emerge as comorbidities of central obesity [ 11 , 14 , 17 , 33 ]. Regarding to hypertension, the increasing trend of elevated blood pressure levels in childhood and adolescence in terms of primary hypertension has been mainly related to the also increasing trend of childhood obesity, but also to other factors such as prenatal and postnatal exposures, genetic factors, birth characteristics, dietary habits, or lifestyle factors [ 50 ]. Some of them have been shown to be related to primary hypertension independently of obesity, as evidenced for example by Rosner et al [ 51 ] in the case of high sodium intake.…”
Section: Discussionmentioning
confidence: 99%
“…Гиподинамия способствует повышению АД. Дети с недостаточной физической активностью примерно в 3 раза чаще имеют избыток массы тела / ожирение и повышенное АД [28]. Установлено, что регулярная физическая активность приводит к значительному снижению АД не только при офисном измерении, но и при 24-часовом контроле.…”
Section: физическая активностьunclassified
“…Low-potassium diet has been associated with elevation of blood pressure in children (1)(2)(3) , which poses an increased risk of childhood hypertension and CVD in adulthood (4,5) . Some studies have showed that daily potassium intake in children is commonly less than the recommended levels (6) .…”
mentioning
confidence: 99%